Photo history by numbers: charting the rise and fall of commercial photography in Cameroon - Zeitlyn, D (Taylor & Francis, 2019)
In this paper I provide baseline estimates for the scale of black-and-white photography as a locally run, commercial undertaking in Cameroon both before and after independence. In categorizing, starting with short 19th and 20th centuries, I end by suggesting a better division is between an era of Colonial Photography (roughly 1865-1955) and a shorter period of larger-scale Administrative Photography (1955-1985), the so-called “Golden Age of the Studios.” I estimate that the number of commercial photographers there had grown to approximately 1,400 by 1985, with a cumulative total of more than 3,500 photographers. These figures provide a context for the detailed discussion of any one photographer, where it is important to know, for example, whether he/she was one in ten or one in a thousand.